Gender differences in computer and information literacy: An exploration of the performances of girls and boys in ICILS 2013. (November 2017) - Punter, R Annemiek; Meelissen, Martina RM; Glas, Cees AW
IEA's International Computer and Information Literacy Study (ICILS) 2013 showed that in the majority of the participating countries, 14-year-old girls outperformed boys in computer and information literacy (CIL): results that seem to contrast with the common view of boys having better computer skills. This study used the ICILS data to explore whether the achievement test used in this study addressed specific dimensions of CIL and, if so, whether the performances of girls and boys on these subscales differ. We investigated the hypothesis that gender differences in performance on computer literacy items would be slightly in favour of boys, whereas gender differences in performance on information literacy items would be slightly in favour of girls. Furthermore, it was examined whether such differences varied across European countries and if item bias was present. Data was analysed using a confirmative factor analysis model, i.e. a multidimensional item response theory model, for the identification of the subscales, the explorations of gender and national differences, and possible item bias. To a large extent the results support our postulated hypothesis and shed new light on the commonly assumed disadvantaged position of girls and women in modern information society.